The interculturality and cultural survival.: Creation and Research Strategy in the GEXPEMO-YUMA seedbed (The Voz a Vos Bulletin, 2022)
From the concept of Interculturality, understood as a mediator in context situations, where there is great cultural baggage that affects one another, the GEXPEMO-DANZAS YUMA seedbed, given its geographical location in the city of Barrancabermeja, works from the multiculturalism, where praxis with theory is evidenced by having different corporalities that have preferably acquired skills from other popular and urban languages, which as teachers we have potentiated and have developed creative strategies mediating with these new corporeal languages, in order to give priority to local culture.There is no doubt that these interculturalities in the first instance occur due to the constant migration of populations due to economic factors and in other circumstances due to public order issues. However, this allows the growth of interculturality in contexts that sometimes displace their own culture, therefore, as research teachers, strategies have been generated to maintain and claim the culture of the territory, respecting and taking elements of urban cultures, to put them in dialogue with local culture.This has allowed the creation process of the GEXPEMO-Yuma seedbed to give good results, since, the training of trainers, allows the student to have that transdisciplinary perspective and see the possibilities of rhythm and didactic strategies for teaching folk dance.
Keywords: Interculturality, creation, research seedbeds.